Automedicação no Brasil: dimensões de uma prática - Fernandes, Maria Eneida Porto (2018)
The drugs are important social assets, being considered as strategic inputs in the development of health actions. They have, in recent years, the magnification of your availability, quality and rational use, implemented in Brazil, by governmental initia-tives through pharmaceutical policies. In spite of the advances, it finds obstacles in your execution, since there are still in the country difficulty of access, delay and ques-tionable quality in the provision of the health services offered to the population. It is added to these aspects, the marketing practices, the ease acquisition of the prod-ucts, allied to the belief that the medicines all solve, being important factors for the exercise of the self-medication. Centralized in this treatment alternative, the purpose of this study is to analyze the prevalence and factors associated with self-medication in Brazil. Based on a cross-sectional population-based survey, the study was con-ducted using data from the National Survey on Access, Use and Promotion of Ra-tional Use of Medicines (PNAUM) from September 2013 to February 2014, through 41433 household interviews in the five regions of the Brazil. All people who reported using any non-prescription medication by physician or dentist were classified as self-medication practitioners. Gross and adjusted prevalence ratios (Poisson regression) and their respective confidence intervals were calculated. 95% in the investigation of the factors associated to the consumption of drugs by self-medication. The preva-lence of self-medication in Brazil was 16,1% (95% CI 15.0-17.5), being higher in the Northeast region (23,8%, 95% CI 21.6-26.2). After adjusted analysis, self-medication was associated with the female gender, belonging to the age groups 10-19 years, 20-29 years, 40-59 years and 60 years or more, living in the North, Northeast or Midwest regions, and have one or two or more chronic diseases. The analgesics, muscle re-laxants, anti-inflammatory and antirheumatic were the most used therapeutic groups for self-medication, with metamizole (15.4%)being the drug with the highest con-sumption. Overall, most of the drugs used for self-medication were classified as non-prescription, as OTC (65,5%). It can be concluded that self-medication is current practice in Brazil and mainly involves the use of non-prescription drugs, and users should be aware of their possible risks.